Social Media Flexing, Self-Presentation, and Conspicuous Consumption: A Phenomenological Study of Generation Z University Students - YUNIAR MUJIWATI; HANUM FITRI HANIFAH (Jurnal Moral Kemasyarakatan, 2026)
The phenomenon of "flexing" on social media is increasingly prevalent among Generation Z university students; however, previous studies have generally examined self-presentation and consumerist behavior in isolation. This study offers a novel contribution by integrating these concepts and revealing the underlying attitude-behavior gap. It aims to analyze the influence of flexing on the self-presentation strategies, social identity construction, and consumerist behaviors of Generation Z students. A descriptive phenomenological qualitative approach was employed, utilizing semi-structured interviews with 36 students from Universitas PGRI Wiranegara selected through purposive sampling. Data analysis was grounded in Self-Presentation Theory and Social Identity Theory. The results indicate that flexing serves as a self-presentation strategy driven by the need for social validation and the fear of missing out (FOMO). Although respondents acknowledged the negative impact of flexing, they continued to exhibit consumerist behaviors. These findings underscore the importance of strengthening digital literacy and self-regulation to mitigate the gap between attitudes and behaviors.